Insta-Health: The Multimodal-Social Semiotic Analysis of WHO’s COVID-19 Promotion Campaign Posters - Ihza Amalia Farahdina; Suhandoko Suhandoko (Universitas Brawijaya, 2023)
The study aimed to provide an in-depth understanding of the messages conveyed by the posters related to COVID-19. Employing descriptive qualitative method, the study analyzed the verbal and visual elements of health promotion posters posted by the World Health Organization’s (WHO) official Instagram, using Halliday’s social semiotic metafunction and Kress and van Leeuwen’s multimodality. The study found that the multimodal posters effectively conveyed messages related to instructions, information, and prohibitions. However, an imbalance in the application of various modes within the posters was identified, posing the potential for misunderstanding and confusion among viewers. Nevertheless, the study offers several suggestions on creating health promotion posters that are both persuasive and informative. The findings contribute to the development of health campaign poster materials that capture attention, convey messages effectively, and align with expectations outlined in health campaign targets, while simultaneously ensuring comprehensive communication. The study provides evaluative results that can inform effective communication strategies for promoting public health during the ongoing COVID-19 pandemic.